2010
DOI: 10.3109/17435391003793095
|View full text |Cite
|
Sign up to set email alerts
|

In vivoeffect of industrial titanium dioxide nanoparticles experimentally exposed to hairless rat skin

Abstract: We morphologically investigated animal skin exposed to W/O emulsion containing 10 wt % ultrafine TiO(2) particles that had been characterized. After 4 h, exposed skin was investigated by light microscopy, confocal laser scanning microscopy (CLSM) and electron microscopy with energy-dispersive X-ray spectrometry (EDX). Light microscopic evaluation was also performed on the exposed skin after 24, 72 and 168 h. Light microscopy did not show any morphological and immunohistochemical changes in the skin. Electron m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 31 publications
1
24
0
Order By: Relevance
“…Some studies showed that nano-TiO 2 features a low, if not negligible, toxicity. [25][26][27][28][29][30][31] In contrast, many other studies indicated that nano-TiO 2 exhibit cytotoxicity and genotoxicity to various cell models such as fibroblasts, macrophages, keratinocytes, epithelial cells, and liver cells. 2,25,32,33 As stated above, the mechanism of cytotoxicity induced by different types of nanoparticles is complex and is yet to be fully understood.…”
Section: Introductionmentioning
confidence: 97%
“…Some studies showed that nano-TiO 2 features a low, if not negligible, toxicity. [25][26][27][28][29][30][31] In contrast, many other studies indicated that nano-TiO 2 exhibit cytotoxicity and genotoxicity to various cell models such as fibroblasts, macrophages, keratinocytes, epithelial cells, and liver cells. 2,25,32,33 As stated above, the mechanism of cytotoxicity induced by different types of nanoparticles is complex and is yet to be fully understood.…”
Section: Introductionmentioning
confidence: 97%
“…Because large amounts of TiO 2 nanoparticles are used in pharmaceutical and skin care products, there is great potential for them to be ingested and impact people's health (Adachi et al, 2010; Burnett and Wang, 2011; Kiss et al, 2008; Liu et al, 2010; Long et al, 2006; Sadrieh et al, 2010; Schulz et al, 2002; Wu et al, 2009). In order to use them advisably, it is important to know the interaction mechanisms between bio‐nanomaterials and cells.…”
Section: Introductionmentioning
confidence: 99%
“…In light of these results, we can explain the findings of Adachi et al [11] and Sadrieh et al [22]. The exposure concentrations in their experiments were too low to cause cell membrane destabilization and subsequent cellular internalization.…”
Section: Discussionmentioning
confidence: 52%
“…Adachi et al [11] reported that no TiO 2 particles could be found in viable skin, and the findings of Sadrieh et al [22] also indicate no significant penetration of TiO 2 nanoparticles through the intact normal epidermis. Adachi et al [11] reported that no TiO 2 particles could be found in viable skin, and the findings of Sadrieh et al [22] also indicate no significant penetration of TiO 2 nanoparticles through the intact normal epidermis.…”
Section: Discussionmentioning
confidence: 98%